Ganglionar metastization on radical prostatectomy. - Reis, Mário (2004)
To analyze retrospectively 19 patients with positive pelvic lymph node disease obtained with a radical prostatectomy. To discuss the actual role of pelvic lymphadenectomy and evaluate the results obtained using one treatment protocol.Between January 1993 and December 2001 450 patients underwent radical prostatectomy for localized prostate cancer. Nineteen patients were identified as having positive ganglionar disease (4.2%). The mean PSA value of the 450 patients was 11.8 ng/ml (ranging 1.9 - 40 ng/ml). We analyzed the survival curves using the method of Kaplan-Meier, based on non recurrence of elevated biochemical total PSA values. The mean follow up time was 37.7 months. The recurrence of disease was defined by two consecutive determinations of PSA values greater than 0.2 ng/ml. Results: the mean age of the nineteen patients was 66 years, varying between 56 and 74. The specific survival curve for these patients shows a survival probability of 60.9%, after 5 years. The survival curve of biochemical free recurrence shows a probability of 37.5%, after 5 years.A progressive decrease in the incidence of patients with ganglionar disease was observed after radical prostatectomy. It is therefore disputable the role of routine lymphadenectomy, its advantages, disadvantages and indications. The scientific analysis have permited great controversy regarding treatment. Our results with a treatment protocol which utilizes preventive adjuvant radiotherapy together with hormone treatment, initially differed and actually systematic, shows a survival rate similar to other studies.The actual indication of lymphadenectomy is maintained in radical retropubic prostatectomy and in patients with a risk of extracapsular disease in perineal prostatectomy or laparoscopy prostatectomy. The monotherapy offers a limited potential of cure. An extensive disease needs an aggressive therapy. A combination of adjuvant radiation therapy and simultaneous hormone treatment is indicated until there exists a randomized study, with an adequate follow up time, to determine which treatment strategy is the best.